2017
DOI: 10.1186/s12883-017-0865-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of fibrinogen level with early neurological deterioration among acute ischemic stroke patients with diabetes

Abstract: BackgroundDiabetes mellitus (DM) is a risk factor for early neurological deterioration (END) in acute ischemic stroke. The prothrombotic protein fibrinogen is frequently elevated in patients with diabetes, and may be associated with poorer prognoses. We evaluated whether fibrinogen is associated with END in patients with diabetes after acute ischemic stroke.MethodsWe included 3814 patients from a single hospital database admitted within 72 h of onset of ischemic stroke. END was defined as an increase in the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 39 publications
5
44
0
Order By: Relevance
“…However, early neurological deterioration (END) may occur to a fraction of patients with AIS, even though they take antiplatelet agents and statins regularly [8][9][10]. Previous studies showed that the incidence of END in AIS patients ranges from 5% to 40%, which might depend on different inclusion criteria and evaluation methods [8][9][10][11][12]. It is reported that END could lead to elevated probability of death and disability in AIS patients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, early neurological deterioration (END) may occur to a fraction of patients with AIS, even though they take antiplatelet agents and statins regularly [8][9][10]. Previous studies showed that the incidence of END in AIS patients ranges from 5% to 40%, which might depend on different inclusion criteria and evaluation methods [8][9][10][11][12]. It is reported that END could lead to elevated probability of death and disability in AIS patients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…As previously described [11], a more sensitive END criterion was incorporated in the current study to improve the awareness of subtle clinical changes that may require clinical intervention. END was defined as an increase in the NIHSS score within 3 days after admission compared with the baseline NIHSS score, including the following scenarios: (1) ≥2 increases in the total NIHSS score; (2) ≥1 increase in specific sub-items on the NIHSS, namely, consciousness level (1a-1c) or movement ability (5a-6b); or (3) new onset neurological deficits despite no NIHSS score changes.…”
Section: Definition Of Endmentioning
confidence: 99%
“…Therefore, it may play crucial role in the pathogenesis of cardiovascular disease. According to the recent literature, elevated levels of plasma FIB indicate an increased risk of cerebral infarction, coronary heart disease, and peripheral vascular disease in individuals …”
Section: Introductionmentioning
confidence: 99%
“…According to the recent literature, elevated levels of plasma FIB indicate an increased risk of cerebral infarction, coronary heart disease, and peripheral vascular disease in individuals. 20,21 At present, the diagnosis of ACI is mainly based on imaging findings, such as computed tomography (CT) or magnetic resonance imaging (MRI) scans, but it is difficult to equip such expensive equipment in the emergency department of most medical institutions. Furthermore, many primary hospitals still lack such equipment.…”
mentioning
confidence: 99%